2022
DOI: 10.3390/ma15207073
|View full text |Cite
|
Sign up to set email alerts
|

Concrete Performance Attenuation of Mix Nano-SiO2 and Nano-CaCO3 under High Temperature: A Comprehensive Review

Abstract: Fire and extreme heat environmental changes can have an impact on concrete performance, and as climate change increases, new concrete structures are being developed. Nano-silica and nano-calcium carbonate have shown excellent performances in modifying concrete due to their large specific surface areas. This review describes the changes in concrete modified with nano-silica (NS) and nano-calcium carbonate (NC), which accelerate the hydration reaction with the cementitious materials to produce more C-S-H, result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 121 publications
(122 reference statements)
1
2
0
Order By: Relevance
“…It is evident from these results that adding nanoparticles to the concrete mixture produced less k coefficient composite. This is consistent with the results of previous studies (Saleh et al, 2021;Nazari and Riahi, 2011;Oh et al, 2023;Ren et al, 2018;Khaloo et al, 2016;Syamsunur et al, 2022). It can be concluded that adding some of the nano-SiO 2 as a cement substitute has positive economic effects due to its merits; nano-SiO 2 is a desirable, reliable, and inexpensive substitute compared to other nanomaterials.…”
Section: Thermal Conductivity (K Coefficient) Resultssupporting
confidence: 91%
“…It is evident from these results that adding nanoparticles to the concrete mixture produced less k coefficient composite. This is consistent with the results of previous studies (Saleh et al, 2021;Nazari and Riahi, 2011;Oh et al, 2023;Ren et al, 2018;Khaloo et al, 2016;Syamsunur et al, 2022). It can be concluded that adding some of the nano-SiO 2 as a cement substitute has positive economic effects due to its merits; nano-SiO 2 is a desirable, reliable, and inexpensive substitute compared to other nanomaterials.…”
Section: Thermal Conductivity (K Coefficient) Resultssupporting
confidence: 91%
“…It is essential to accurately and promptly predict the durability of HPC (Pengcheng et al 2020). Over the past few decades, nanotechnology has proven to be a competitive means of increasing the durability and strength of construction materials (Syamsunur et al 2022). The term nanotechnology describes the process of creating, assembling and applying functional structures that have a minimum of one feature dimension expressed in nanoscale units.…”
Section: Introductionmentioning
confidence: 99%
“…The nanocracks then grow into micro-and macrocracks, which adversely affect the mechanical and durability properties [24]. Graphene oxide, silica, titanium oxide (TiO 2 ), iron (Fe 2 O 3 ), alumina oxide (Al 2 O 3 ), CuO, calcium carbonate, ZnO 2 , and ZrO 2 have been used during the last years in cement and concrete [25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%